GENETIC VARIABILITY OF PERSPECTIVE BTREEDING MATERIAL OF SPRING BREAD WHEAT FOR RESISTANCE TO LEAF RUST IN RUSSIA AND KAZAKHSTAN - Gultyaeva Elena,; Kokhmetova Alma,; Shaydayuk Ekaterina,; Shreyder E.R.,; Atishova Makpal,; Madenova Aigu,; Kanat Galymbek,; Malysheva Angelina, (Scientific Journal of Pedagogy and Economics, 2020)
Leaf rust, caused by Puccinia triticina Erikss., is one of the major diseases of wheat in Russia and Kazakhstan. The resistance and genetic diversity of 61 spring wheat genotypes from Russia and 50 ones from Kazakhstan were studied. Field evaluation of Kazakhstani wheat material allowed to select 27 lines as resistant and 8 lines as moderate resistant to leaf rust. Molecular screening revealed 29 wheat lines characterized by the presence of Lr genes. As a result of phytopathological and molecular screening of Kazakhstani material, carriers of 2, 3, and 4 Lr genes were selected. The 92 % of Chelyabinsk’ lines were characterized by high level of resistance to leaf rust both at the adult and seedling stages. Using molecular markers Lr24, Lr9, Lr19, LrSp, Lr1, Lr3, Lr10, Lr26, Lr21 and Lr34 genes separately or in different combinations has been revealed in Russian wheat lines. In the field conditions of the Southern Urals, isogenic lines with genes Lr24, Lr25, Lr26, Lr28, Lr45, Lr47, Lr49, Lr51 and Lr57 showed high resistance, and in lines with the genes Lr17, Lr23, Lr29 and Lr64 moderate resistance was observed. At the seedling stage all single pustule isolates were avirulent to Tc-lines with Lr16, Lr19, Lr24, Lr28 and Lr29 genes. In Kazakhstan virulence of P. triticina population collected in South-East and North-Kazakh regions was studied. Against the Almaty population Lr9, Lr19, Lr24, Lr25 and Lr28 genes with high efficacy, and gene Lr45 with moderate efficacy were identified. All of the lines with the rest Lr genes were susceptible to the pathogen. The isogenic lines with genes Lr19, Lr24, Lr25, Lr28, Lr36 and Lr45 were characterized by high efficacy to the Kostanai P. triticina population. Virulence studies of P. triticina showed a similarity of pathogen structure on the Southern Urals of Russia and Northern Kazakhstan.